Molecular mechanism of plant cellulose biosynthesis through structural investigation - Kong, Sean Yao Zu (2017)
Cellulose synthase (CesA), is a membrane-associated protein which has proven to be difficult to purify. In recent years, the crystal structure of the bacterial counterpart of CesA was elucidated. However, at present, the crystal structure of plant CesA is still an enigma, and we only have predicted structures. Since many fundamental differences exist between plant CesA and bacterial CesA this gives us reason to look for answers through crystallising the protein. In this study, there are two main goals. The first goal is to prepare sufficient stable proteins for crystallisation. To do this, various truncations of the CesA catalytic domain and homolog screenings were performed. The second goal is to crystallise the protein by performing crystal screening and surface residue mutations. Site-directed mutagenesis was performed on the catalytic domain of wild-type Arabidopsis thaliana (At) cesa8 gene to facilitate protein-protein crystal contacts. Even though the purified mutant AtCesA8 protein could not be crystallised, we found a truncation of CesA catalytic domain with higher thermal stability. Using sequence homology, a homolog of CesA protein was generated from Hordeum vulgare(Hv) and results show it was the best in terms of purification and yield. This advancement brings us closer to finally crystallising this protein.